2011
DOI: 10.1021/pr200758q
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Identification of Bacteria–Host Crosstalk by Affinity Chromatography: Capturing the Interactions of Streptococcus suis Proteins with Host Cells

Abstract: Protein-protein interactions between bacteria and their hosts are responsible for all types of infection processes. The investigation of the bacteria-host crosstalk can provide a comprehensive understanding of the pathogenesis of bacterial disease. Despite scattered efforts in this field, a systematic identification of interactions between host and bacterial proteins remains unavailable. Here, we develop ACSP (affinity chromatography-based surface proteomics), which combines affinity chromatography and shotgun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 70 publications
0
19
1
Order By: Relevance
“…These were proposed as vaccine candidates especially as they are reasonably conserved among S. suis strains [93]. A combination of affinity chromatography and surface proteomics using LC-MS/MS [94] has identified 40 potential surface interacting proteins of S. suis although the majority of the identified proteins were intra-cellular rather than cell wall in origin and also showed that eight proteins further investigated were involved in the bacteria binding to Hep-2 cells.…”
Section: Bacterial Diseasesmentioning
confidence: 99%
“…These were proposed as vaccine candidates especially as they are reasonably conserved among S. suis strains [93]. A combination of affinity chromatography and surface proteomics using LC-MS/MS [94] has identified 40 potential surface interacting proteins of S. suis although the majority of the identified proteins were intra-cellular rather than cell wall in origin and also showed that eight proteins further investigated were involved in the bacteria binding to Hep-2 cells.…”
Section: Bacterial Diseasesmentioning
confidence: 99%
“…Recently high-throughput proteomic analysis has been applied for identification of relevant host–pathogen protein–protein interaction [ 22 , 23 ]. Moreover, affinity chromatography combined with shotgun proteomics analysis has been practiced for investigating the interactions between Streptococcus suis proteins and host cells [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Suilysin, the extracellular protein factor, along with a muramidase-released protein have also been shown to be linked to, but not essential for, the full virulence of S. suis [21]. GapdH [22], Enolase [23], [24], Fibronectin/Fibrinogen-binding protein [25], HAM1 [26] and Adhesion [27], [28], [29], [30], [31], [32] have been shown to be involved in S. suis adherence and virulence. Serum opacity-like factor [33], D-Alanylation of Lipoteichoic Acid [34], Peptidoglycan GlcNAc deacetylase [35], IgA protease [36], [37], TroA [38], SodA [39], SsFHB [40] and Subtilisin-like serine protease [41], [42], [43] are also considered to be related to S. suis virulence.…”
Section: Introductionmentioning
confidence: 99%